Answer:
10
Step-by-step explanation:
The simplified expression for 6(2( y + x)) is 12y + 12x.
Accordin to the given question.
We have an expression
6(2( y + x))
Therefore,
The simplified expression for 6(2( y + x)) is given by
6(2(y + x))
= 6(2y + 2x) (by distributive law)
= 12y + 12x (by distributive law)
Hence, the simplified expression for 6(2( y + x)) is 12y + 12x.
Find out more information about simplified expression here:
brainly.com/question/18077352
#SPJ4
Answer:
1/12
Step-by-step explanation:
dice rolling=1/6
coin flipping=1/2
Hence probability=1/6×1/2
Answer:
The answer is c
Step-by-step explanation:
My original answer got deleted i dont know the reason.
Answer:
21
Step-by-step explanation: